Analytical data for Ti, Mo, and Pb in selected nodules from different stations in the Aitutaki Passage - Geoffrey P Glasby; Theo Thijssen; W L Plüger; Günther Friedrich; Augusto Mangini; Peter Stoffers; J Dominik; G Frenzel; J E Andrews; G S Roonwal (PANGAEA, 2023)
Manganese nodules and crusts from stations of the SO06 expedition (R/V Sonne) in the Aitutaki Passage have been selected for chemical analysis of Ti, Mo and Pb using atomic absorption spectrophotometry. Material has been dried before analysis at 105°C for 72 hrs and results are presented as averages over various size fractions.